2010
DOI: 10.1016/j.sjbs.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of BTEX in groundwater by using gas chromatography–mass spectrometry

Abstract: Advanced analytical modern technology such as coupling a gas chromatography to a mass spectrometric technique provides sufficient information to the environmental and analytical chemists to identify the presence of a variety of components of the specific volatile organic product, determine the degree of the product weathering and in some instances estimate the age of the product as well in the testing sample. In this study, we estimated BTEX in groundwater sample by using gas chromatography-mass spectrometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…15 Estimation of BTEX in groundwater using a combination of gas chromatography and mass spectrometry was also reported. 16 Although these methods are capable of accurately quantifying BTEX compounds, there are several drawbacks associated with these techniques. For instance, while Raman spectroscopy 15 can be made field-deployable, its portable version lacks the necessary detection limits for BTEX compounds (i.e., BTEX detection limits are relatively high on the order of several ppm).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Estimation of BTEX in groundwater using a combination of gas chromatography and mass spectrometry was also reported. 16 Although these methods are capable of accurately quantifying BTEX compounds, there are several drawbacks associated with these techniques. For instance, while Raman spectroscopy 15 can be made field-deployable, its portable version lacks the necessary detection limits for BTEX compounds (i.e., BTEX detection limits are relatively high on the order of several ppm).…”
mentioning
confidence: 99%
“…The conventional techniques used to detect and quantify BTEX compounds involve either spectroscopy or gas chromatography. , Examples include infrared evanescent field spectroscopy and Raman spectroscopy . Estimation of BTEX in groundwater using a combination of gas chromatography and mass spectrometry was also reported . Although these methods are capable of accurately quantifying BTEX compounds, there are several drawbacks associated with these techniques.…”
mentioning
confidence: 99%
“…A large number of studies related to Fenton-based methods have been carried out at room temperature [39,[75][76][77]. This is because thermal decomposition of H 2 O 2 occurs at temperatures above 50°C [78][79][80][81][82][83][84]. In addition, due to the fact…”
Section: Temperaturementioning
confidence: 99%
“…that H 2 O 2 decomposition is accelerated at basic pH values, the increment in temperature brings about a shift in optimum pH towards acidic values [39,75,80]. In fact, a study [71] reported an optimum temperature of 30°C, whereas another study [55] reported that the degradation efficiency is unaffected even when the temperature is increased from 10 to 40°C.…”
Section: International Journal Of Environmental Sciences and Natural Resourcesmentioning
confidence: 99%
“…Benzene, toluene, ethyl benzene and xylene (BTEX) are widespread pollutants of which the main source in the outside environment is vehicle traffic and indoor the cigarette smoke. They are also present in small quantities in drinking water and food, in painting substances or adhesives [3].…”
Section: Introductionmentioning
confidence: 99%